Topological perception on attention to product shape. Issue 2 (2nd April 2020) - Fei, Fei; Nagai, Yukari
ABSTRACT: A primitive and general function of the visual system is the perception of global topological properties. In fact, people prioritize attention to these properties over the local geometric properties of an object. In this study, we aimed to verify whether the perception of topological properties is applicable to product recognition. If a topological transformation occurs in the shape of a product, the product may receive more attention from customers and improved publicizing of the product's innovative and nonvisual characteristics, such as function and experience, can be inferred. Therefore, topological properties may contribute to product innovation. We hypothesized that perceiving topological properties (e.g. holes, connectivity, and inside/outside relationships) occurs in product shapes, and human attention to products varies according to topological transformations in these shapes. Experimental results on bicycle recognition suggest that human attention varies according to topological transformations. A repertory grid was used to discover and discriminate the reasons for such variations. We extracted the mental constructs of the participants regarding the products with different topological transformations and identified the main reasons for visual attention. People pay more visual attention to the shapes of products with clear topological variations.